Manajemen Sarana dan Prasarana di Dayah Ar-Raudhah Lhokseumawe - Regita Keumala Sabty; Muna Afra; Agus Salim Salabi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the management of facilities and infrastructure at Dayah Ar-Raudhah Lhokseumawe, a traditional Islamic educational institution in Aceh. As an institution that combines Islamic values with a pesantren-based education system, adequate facilities and infrastructure are crucial for supporting the teaching and learning process and fostering the character of its students. This study uses a qualitative descriptive approach to comprehensively describe how the management of facilities such as classrooms, dormitories, mosques, public kitchens, and libraries is carried out practically and contextually. Data were obtained through direct observation and in-depth interviews with the dayah leadership, facility managers, and students, complemented by visual documentation. The results indicate that limited operational funds are a major obstacle hindering the optimal development of facilities and infrastructure. Furthermore, the lack of professional technical personnel also hinders the ongoing maintenance of facilities. However, the active participation of students and dayah staff in environmental maintenance and cleanliness activities has a positive impact on facility utilization. Routine mutual cooperation activities, a sense of shared responsibility, and a religious approach to maintaining cleanliness and well-being are unique strengths of Dayah Ar-Raudhah. This study recommends several strategic steps, such as partnering with external parties for fundraising, technical training for staff and students, and developing an internal educational program that emphasizes the importance of facility maintenance as part of Islamic values. This participatory, values-based management model is expected to inspire and serve as a reference for other dayahs in the Aceh region in building healthy, clean, and sustainable learning environments.